Alterations in Serum Levels of Trace Elements in Cutaneous Leishmaniasis Patients in Endemic Region of Hatay (Antioch) - CULHA, GULNAZ; YALIN, ERDINC; SANGUN, KEMAL (Asian Journal of Chemistry, 2010)
Immune cells, like all other types of cells, require an adequate supply of trace elements for the structure and function of metalloproteins that participate in housekeeping processes such as energy production and protection against reactive oxygen species. In addition, trace elements are required for the activity of a number of enzymes that directly participate in host defense processes. In the present study we evaluated the alterations of zinc, copper, selenium and iron concentrations in serum of patients treated with meglumine antimonate (glucantime) and untreated cutaneous leishmaniasis. Serum levels of zinc, copper, selenium and iron were measured by atomic emission spectrometer. The serum levels of these elements were found to be significantly higher in untreated patients compared to those of healthy controls. However, the levels of zinc, copper and iron in serum were significantly reuced and selenium levels were increased in treated patients. These suggest that the increasing levels of trace elements in serum may be host defense strategies of organism infection. In addition the high trace element levels were a sequel of the disease rather than a cause.